Clinical Epidemiology of Hospitalized Patients With Coronavirus Disease 2019 (COVID-19) in Japan: Report of the COVID-19 Registry Japan. (28th September 2020) - Matsunaga, Nobuaki; Hayakawa, Kayoko; Terada, Mari; Ohtsu, Hiroshi; Asai, Yusuke; Tsuzuki, Shinya; Suzuki, Setsuko; Toyoda, Ako; Suzuki, Kumiko; Endo, Mio; Fujii, Naoki; Suzuki, Michiyo; et al.
Abstract: Background: There is limited understanding of the characteristics of patients with coronavirus disease 2019 (COVID-19) requiring hospitalization in Japan. Methods: This study included 2638 cases enrolled from 227 healthcare facilities that participated in the COVID-19 Registry Japan (COVIREGI-JP). The inclusion criteria for enrollment of a case in COVIREGI-JP are both (1) a positive severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) test and (2) inpatient treatment at a healthcare facility. Results: The median age of hospitalized patients with COVID-19 was 56 years (interquartile range [IQR], 40–71 years). More than half of cases were male (58.9%, 1542/2619). Nearly 60% of the cases had close contact to confirmed or suspected cases of COVID-19. The median duration of symptoms before admission was 7 days (IQR, 4–10 days). The most common comorbidities were hypertension (15%, 396/2638) and diabetes without complications (14.2%, 374/2638). The number of nonsevere cases (68.2%, n = 1798) was twice the number of severe cases (31.8%, n = 840) at admission. The respiratory support during hospitalization includes those who received no oxygen support (61.6%, 1623/2636) followed by those who received supplemental oxygen (29.9%, 788/2636) and invasive mechanical ventilation/extracorporeal membrane oxygenation (8.5%, 225/2636). Overall, 66.9% (1762/2634) of patients were discharged home, while 7.5% (197/2634) died. Conclusions: We identified the clinical epidemiological features of COVID-19 in hospitalized patients in Japan. When compared with existing inpatient studies in other countries, these results demonstrated fewer comorbidities and a trend towards lower mortality. Abstract : Registry data of 2638 hospitalized COVID-19 cases revealed that mechanical ventilation was required in 8.5% of cases, and the overall mortality was 7.5%. Results of this study demonstrated fewer comorbidities and lower mortality than existing inpatient studies in other countries.